2022
DOI: 10.3390/su141811256
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Residential Satisfaction in Resettlement Housing in Ellembelle: A PLS-SEM Approach

Abstract: Compensation for land expropriation due to development projects such as mining is shifting from cash to physical assets like housing. Therefore, empirical studies are required to assess the residential satisfaction of project-affected families (PAFs) living in these houses and the factors which can enhance their satisfaction and quality of life in the long term. This study, therefore, assesses the antecedents of PAFs’ satisfaction with their current residence as an outcome of a mining-induced displacement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…When developing homes and making plans for the resettlement community, it must be a key concern to create conditions that meet the needs of MAFs. These findings are consistent with what other research has shown, which is that MAFs are happier at home and have a higher QoL when their house's surroundings are enhanced [15,17,[51][52][53][54].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When developing homes and making plans for the resettlement community, it must be a key concern to create conditions that meet the needs of MAFs. These findings are consistent with what other research has shown, which is that MAFs are happier at home and have a higher QoL when their house's surroundings are enhanced [15,17,[51][52][53][54].…”
Section: Discussionsupporting
confidence: 92%
“…The quality of resettlement may have an impact on MAFs' QoL depending on how satisfied they are with their residences [15,17,49]. The qualities of the neighborhood and the house were used in this study to determine the quality of resettlement housing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Housing inequality caused by governmental housing regimes lies at the root of socio-spatial segregation and exclusion in most cases [1][2][3][4][5][6]. This issue has been increasingly recognized as a corrodent to the social resiliency of cities and is a threat to human health [7][8][9] and people's life satisfaction [10][11][12][13][14]. This is especially true in the Chinese context, in which a unique political system and institutional forces operate, such as housing reform, which has played a critical role in many aspects of residents' lives [15].…”
Section: Introductionmentioning
confidence: 99%